Characteristics of the Sharia Supervisory Board, Board of Commissioners and Board of Directors on the Profitability of Islamic Banking in Indonesia - Febriyanti, Elsa; Wijayanti, Rahma (SMART Insight, 2024)
This research aims to analyze the influence of board characteristics on the profitability of Islamic banking in Indonesia as measured using Return On Assets (ROA). The independent variables, namely the characteristics of the sharia supervisory board, board of commissioners and board of directors are associated with board size, board educational background and board tenure with firm size as a control variable, while the dependent variable is the profitability of sharia banks. This research uses a quantitative approach with descriptive methods and panel data regression analysis. Based on research results, the size of the sharia supervisory board, board of commissioners and board of directors has no effect on the profitability of sharia banking. The educational background of the sharia supervisory board and board of commissioners has no effect on the profitability of sharia banking, while the educational background of the board of directors has a positive and significant influence on the profitability of sharia banking. The term of office of the sharia supervisory board, board of commissioners and board of directors has no effect on the profitability of sharia banking.